Asynchronous risk: Unemployment, equity markets, and retirement savings - Jason S. Seligman; Jeffrey B. Wenger (W.E. Upjohn Institute for Employment Research, 2005)
The link between unemployment and pension accumulations is conceptually straightforward; periods of unemployment lead to lower pension contributions, and thus to lower accumulations. However, impacts on accumulation may differ as a result of the timing and frequency of unemployment spells. We hypothesize that unemployment is more likely during periods in which the equities market experiences greater than average returns, largely due to a lead/lag structure of the stock and labor markets, respectively. This would imply that workers may systematically miss opportunities to purchase equities through DC plans when prices are relatively low. To test this hypothesis, we match historic stock returns to stochastically generated unemployment spells for men and women across the earnings distribution. We find lower income workers suffer greater percentage losses in retirement savings as a result of more frequent spells of unemployment. Higher income worker losses are more greatly affected by the timing of unemployment relative to the equities market.
Keywords: 330; unemployment; retirement; savings; defined contribution; pensions; earnings distribution; Arbeitslosigkeit; Alterssicherung; Sparen; Aktienmarkt; Kapitalertrag; USA